Penerapan Manajemen Risiko Operasional Dalam Upaya Meminimalisir Kesalahan Sumber Daya Insani di BMT Istiqomah Plosokandang Tulungagung - Fatkhur Rohman Albanjari; Hanum Willyan Dinara (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
This research aims to analyze the implementation of operational risk management in efforts to minimize human resource errors at BMT Istiqomah Plosokandang Tulungagung. The research method used was descriptive qualitative, and the data collection method was carried out through direct interviews with Mr. Imam Mustakim, located at the BMT Istiqomah Unit 2 Plosokandang office.The research results show that the treatment taken to avoid bankruptcy is to use a modern digital system and be careful with prospective members and the form of responsibility borne by the person concerned when a problem occurs; establishing good relations with members and the surrounding community and participating in community activities by donating funds so that BMT Istiqomah is not underestimated; and BMT Istiqomah Unit 2 applies honesty, fairness, transparency and good trust so that leadership management can run smoothly.